The Effect of Concentration of Kecombrang Flour and Storage Duration on Physical and Chemical Properties of Cuko Pempek - Mukhtarudin Muchsiri; A. Alhanannasir (Universitas Muhammadiyah Surakarta, 2018)
storage duration on the physical and chemical properties of dark sauce, best-known as cuko pempek. A randomized block design was used and divided into two stages of implementation. In the first stage, the bioactive or phytochemical compounds contained in cuko pempek were generated, namely phenol and tannin. The average amount of phenol in cuko pempek is 157.762 ppm while the amount of tannin was 3.132 ppm. The organoleptic assessment was done based on the criteria of color, aroma, and taste of cuko pempek added with kecombrang’s flower flour. In the second stage, the mean pH and total acid of cuko pempek with storage duration of 30-days was 4.14 and 0.67%, respectively. In overall, the organoleptic assessment on color was 3.27; aroma was 3.02 with criteria of like, and flavor was 2.88 with criteria of moderately like. The best treatment was gained by a concentration of 2.5% with storage duration until 30 days.